Enhanced thermal and mechanical properties of Li–Al–Si composites with K2O–B2O3–SiO2 glass for LTCC application. Issue 12 (15th August 2019) - Qin, Yang; Zhong, Chaowei; Yang, Hongyu; Qin, Tianying; Yuan, Ying; Tang, Bin; Zhang, Shuren
Abstract: In this study, Li–Al–Si composites with K2 O–B2 O3 –SiO2 (KBS) glass were synthesized by traditional solid-state method, and the phase composition, microstructure, sintering behavior as well as properties were systematically investigated. The specimen with 4 wt % Al2 O3 sintered at 1020 °C exhibited a high thermal conductivity of 10.46 W/(mK) and a flexural strength of 180.23 MPa. The sintering temperature was reduced from 1020 °C to 900 °C using KBS glass frits as sintering additives. The sample with 2.0 wt % KBS, sintered at 900 °C for 2 h, possessed a relatively high thermal conductivity of 9.83 W/(mK), a high flexural strength of 215.09 MPa, and a low dielectric constant of 6.24, thus demonstrating its potential for LTCC application.